2009
DOI: 10.1210/jc.2008-1588
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Recombinant Human Leptin on Visceral Fat, Dyslipidemia, and Insulin Resistance in Patients with Human Immunodeficiency Virus-Associated Lipoatrophy and Hypoleptinemia

Abstract: Leptin treatment was associated with marked improvement in dyslipidemia. Hepatic insulin sensitivity improved and lipolysis decreased. Visceral fat decreased with no exacerbation of peripheral lipoatrophy. Results from this pilot study suggest that leptin warrants further study in patients with HIV-associated lipoatrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 42 publications
7
84
1
3
Order By: Relevance
“…Although we and others recently have shown that leptin administration effectively improves the metabolic profile of subjects who have HAART-associated lipodystrophy (38)(39)(40)(41), the results of this study indicate that metreleptin administration also may be considered as a potential therapy for other immunocompromised disease states in which CD4 + T cells play a critical role. For instance, leptin therapy may help decrease the incidence of infectious disease states.…”
Section: Ex Vivo Pbmcs From Lean Subjectscontrasting
confidence: 67%
“…Although we and others recently have shown that leptin administration effectively improves the metabolic profile of subjects who have HAART-associated lipodystrophy (38)(39)(40)(41), the results of this study indicate that metreleptin administration also may be considered as a potential therapy for other immunocompromised disease states in which CD4 + T cells play a critical role. For instance, leptin therapy may help decrease the incidence of infectious disease states.…”
Section: Ex Vivo Pbmcs From Lean Subjectscontrasting
confidence: 67%
“…These studies have demonstrated significant beneficial effects of leptin administration in disorders of leptin deficiency (ob/ob and generalized lipodystrophy) and have led to the recent approval of recombinant leptin (metreleptin) in Japan for the treatment of lipodystrophy (Chou & Perry 2013) and in the USA for the treatment of generalized lipodystrophy. Fewer trials have evaluated patients with partial lipodystrophy, both non-HIV associated (Simha et al 2012) and HIV associated (Mulligan et al 2009, Magkos et al 2011, but, overall, these trials have shown benefit, albeit less dramatic than that seen in generalized lipodystrophy. The next steps for leptin will likely be in the hands of the broader scientific and clinical investigative community to further define its biology and clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…22,27,52 Similarly, lipoatrophy and leptin deficiency due to wasting inflicted by human immunodeficiency virus infection and treatment of human immunodeficiency virus-infected patients with antiretroviral treatment, are associated with insulin insensitivity and diabetes, both improved by daily leptin replacement. 25,52,[57][58][59] Importantly, these antidiabetic effects of daily leptin replacement manifesting independent of any discernible impact on appetite and weight, involved hypothalamic leptin responsive pathways because mice with conditional leptin receptor knockout in the hypothalamus were diabetic 60 and instillation of leptin receptors selectively in the hypothalamus repressed hyperinsulinemia in the diabetic, leptin receptor mutant rats. 61 Thus, both leptin deficit and leptinopenia-induced insufficient hypothalamic leptin signaling are associated with dysregulation of the glucose-insulin axis.…”
Section: Introductionmentioning
confidence: 99%
“…26,36,37,53,59,75 These procedures were tedious, allowed only short-term delivery, required constant surveillance and were invariably associated with widespread distribution of leptin to targets within and outside the brain into the periphery where leptin was likely to increase the risks for multiple neural and peripheral ailments. 1,9,15,42,70,76,77 An injection of recombinant adenovirus-encoding leptin gene (Ad-lep) produced hyperleptinemia over several weeks suppressed weight gain, adiposity and blood insulin levels in normal adult rats.…”
Section: Introductionmentioning
confidence: 99%